Potential Environmental Factors Affecting Oil-Degrading Bacterial Populations in Deep and Surface Waters of the Northern Gulf of Mexico - Liu, Jiqing; Bacosa, Hernando P.; Liu, Zhanfei (Frontiers in Microbiology, 2017)
Understanding bacterial community dynamics as a result of an oil spill is important for predicting the fate of oil released to the environment and developing bioremediation strategies in the Gulf of Mexico. In this study, we aimed to elucidate the roles of temperature, water chemistry (nutrients), and initial bacterial community in selecting oil degraders through a series of incubation experiments. Surface (2 m) and bottom (1537 m) water, collected near the Deepwater Horizon site, were amended with 200 ppm light Louisiana sweet crude oil and bacterial inoculums from surface or bottom water, and incubated at 4ºC or 24°C for 50 d. Bacterial community and residual oil were analyzed by pyrosequencing and gas chromatography-mass spectrometry (GC-MS), respectively. The results showed that temperature played a key role in selecting oil-degrading bacteria. Incubation at 4°C favored the development of Cycloclasticus, Pseudoalteromonas, Sulfitobacter and Reinekea, while 24°C incubations enhanced Oleibacter, Thalassobius, Phaeobacter, and Roseobacter. Water chemistry and the initial community have also potential roles in the development of hydrocarbon-degrading bacterial communities. Pseudoalteromonas, Oleibacter, and Winowgradskyella developed well in the nutrient-enriched bottom water, while Reinekea and Thalassobius were favored by low-nutrient surface water. We also revealed that the combination of 4°C, crude oil and bottom inoculum was a key factor for the growth of Cycloclasticus, while the combination of surface inoculum and bottom water chemistry was important for the growth of Pseudoalteromonas. Moreover, regardless of the source of inoculum, bottom water at 24°C was a favorable condition for Oleibacter. Redundancy analysis further revealed that temperature and initial community explained 57% and 19% of the variation observed, while oil and water chemistry contributed 14% and 10%, respectively. Overall, this study revealed the relative roles of temperature, water chemistry, and initial bacterial community in selecting oil degraders and regulating their evolution in the northern Gulf of Mexico.